Protein and vitamin B6 intake are associated with liver steatosis assessed by transient elastography, especially in obese individuals - Ferro, Yvelise (Clin Mol Hepatol, 2017)
BACKGROUND/AIMS: Although the detrimental effects of several dietary components on the promotion of nonalcoholic fatty liver disease are well known, no studies have assessed the role of dietary vitamin B6. Moreover, studies on the associations between dietary components or body composition indices and liver steatosis assessed by transient elastography are rare. Our aim was to identify the nutritional factors and anthropometric parameters associated with liver steatosis. METHODS: In this cross-sectional study, we enrolled 168 individuals (35% obese) who underwent a liver steatosis assessment by Controlled Attenuation Parameter measurement and nutritional assessment. RESULTS: Tertiles of vitamin B6 intake were positively associated with hepatic steatosis (B=1.89, P=0.026, confidence interval [CI] 0.03-0.80) as well as with triglycerides, glucose, alanine aminotransferase (ALT), and body mass index . In obese individuals, after multivariable analysis, the Controlled Attenuation Parameter score was still associated with triglycerides, ALT, and total protein intake (B=0.56, P=0.01, CI 0.10-1.02). Participants in tertile I (low intake) had a lower Controlled Attenuation Parameter than those in tertile III (P=0.01). CONCLUSIONS: We found a positive association between hepatic steatosis or Controlled Attenuation Parameter score and vitamin B6/total protein intake, probably related to the high intake of meat. Vitamin B6 might have a pathogenic role related to the increase of hepatic steatosis.